Annual Weeds Add to the Nutritional Level of Forage from Desert Rangelands - Singh, J P; Mondal, B C; Soni, M L; Beniwal, R K (Annals of Arid Zone, 2016)
Annual weeds remain an integral part of the life support system for grazing animals during normal as well as in the feed scarcity periods. Forage samples of 12 annual weeds rated very high by local graziers were evaluated for various nutritional attributes. The crude protein and total carbohydrate contents ranged from 9.5 to 12.6% and 71.4 to 78.7% in the leguminous weeds and from 6.9 to 11.4% and 57.8 to 81.0% in the non-leguminous weeds. The crude protein of major range grasses hardly exceeds 7% and it comes down to 2 to 3% when grasses dry up. The annual weeds thus help in raising the nutritional level of range biomass.